Revetment block - Mohamed, Thamer Ahmed; Alias, Nor Azlina; Megat Mohd Noor, Megat Johari; Ghazali, Abdul Halim; Jaafar, Mohd Saleh; Thanoon, Waleed Abdulmalik; Yahya, Azmi; Yusuf, Badronnisa; Said, Salim (2009)

(untitled)
The present invention provides a block (10) for use in a revetment system comprising a plurality of blocks arranged and interlocked to each other. The revetment system provides an improved and effective method for controlling erosion of coastal, riverside and hill slope areas by providing a more effective inhibiting barrier to wave actions and tidal changes that can disperse and absorb waves during storm and changes of water level. The present invention discloses a block (10) comprising a top surface (11), a bottom surface (12), a first and second opposing side surfaces (14,15) extending from the lateral edges of the top and bottom surfaces, and a third and fourth opposing side surfaces (16, 17) extending from the lateral edges of the top and bottom surfaces. The body of the block (10) is provided with an opening (13) that opens from the top surface (11) through bottom surface (12) and runs parallel to the third side surface (16) and fourth side surface (17). Each block (10) in the revetment system is interlocked with an adjacent block (10) in all directions by way of the double dovetail interlocking arrangement. The double dovetail interlocking arrangement is accomplished by providing two types of keying means on each block (10), the protruding flange (18) and groove (19), wherein each block (10) is provided with a protruding flange (18) of keying means on the first side surface (14) and the second side surface (15), and a groove (19) of keying means on the third side surface (16) and fourth side surface (17).